Geological Cycles of the Flint Hills: Ancient Ice Ages, Sea Levels, and Climate Change - Keith B. Miller (Symphony in the Flint Hills, 2012)
The history of the Earth is dynamic. Though it may not be apparent to us during our short span of life, the surface of the Earth and the life it supports are in a constant state of change---both progressive (directional) and cyclic. Earth history is also vast, with time scales that are hard to grasp. Geologic time is often referred to as “deep time” to emphasize its distinction from time as seen from a human perspective.
Keywords: Florence limestone; mudstone; blue springs shale; cyclothems; geology; Kansas; rocks; history; layers; sedimentary; superposition; strata; flint; sea; Ice Age; glaciers; glacial; climate change; Permian; Pleistocene; Flint Hills; Triassic; Jurassic